Рrinciple of relativity in navigation for example doppler meter speed - Міхалочкін, М.А.; Харченко, В.П. (Proceedings of National Aviation University (archive), 2006)
There is considered in article the analysis of radio navigation system errors, are determined by the requirements accoroling to the movement of receiver, and transmitter, which are located on the moving objects, i.e. by the “relativists” phenomena; is represented the estimation methodic of acceleration using other Doppler’s device and the acceleration of one aircraft relative to another.